Computer Vision and Audition in Urban Analysis Using the Remorph Framework - Nematollahi, Mohammad Ali.; Shahbazi, Samaneh; Nabian, Nashid; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
Artificial Intelligence (AI) is penetrating in all sciences as a multidisciplinary approach. However, adopting the theory of AI including computer vision and computer audition to urban intellectual space, is always difficult for architecture and urban planners. This book overcomes this challenge through a conceptual framework by merging computer vision and audition to urban studies based on a series of workshops called Remorph, conducted by Tehran Urban Innovation Center (TUIC).
Introducing the Question -- Situating the Question in the General Field of Inquiry -- Computer Vision in Urban Studies: Theory, Techniques and Rules of Application -- Computer Audition in Urban Studies: Theory, Techniques and Rules of Application -- Remorph is a pedagogical framework -- Future Trends in "Smart" Urban Analysis.
Keywords: Computational intelligence; Human geography; Artificial intelligence; Signal processing; Buildings -- Design and construction; Computer-aided engineering; Computational Intelligence; Human Geography; Artificial Intelligence; Signal, Speech and Image Processing; Building Construction and Design; Computer-Aided Engineering (CAD, CAE) and Design